Antiacetylcholinesterase Activity of Ventilago denticulata Extracts and its Chemical Constituents - Lomchoey, Natthakaln; Nontakham, Jannarin; Suebsakwong, Parichat; Suksamrarn, Sunit (KKU Science Journal, 2017)
The anti-alzheimer property against enzyme acetylcholinesterase of Thai medicinal plant Ventilago denticulata extracts and its chemical constituents was investigated. Isolation and purification of V. denticulata roots extracts afforded seven known quinone compounds: ventiloquinone I (1), 2–hydroxyislandicin (2), chrysophanol (3), physcion (4), emodin (5), questin (6) and ventilatone A (7) along with a large quantity of a mixture of common plant sterol, long chain fatty acids and tannin. The structures of quinones were assigned from combination of spectral data analysis especially 1D– and 2D NMR technique, and by comparison with the reported data. Compounds 2 and 4 were isolated for the first time from V. denticulata and from the genus Ventilago, respectively. The crude EtOAc extract (IC50 9.3 ± 0.0001 µg/mL) revealed about 4 times more potent anti–AChE ability than that of the MeOH soluble fraction (IC50 36.3 ± 0.0003 µg/mL), and only compound 7 exhibited effective inhibitory activity at IC50 value of 21.99 ± 0.14 µM.